SERIC MYELOPEROXIDASE ASSOCIATION WITH CARDIOMETABOLIC VARIABLES IN TWO POPULATIONS: CARHUAMAYO (4100 M - JUNIN) AND MALA (30 M - LIMA) - Carreño, María R (2017)
The aim of this study was to determine serum myeloperoxidase (MPO) level, an enzyme considered as an inflammation indicator, in a high altitude population and in another at sea level, and establish the association of this enzyme with risk factors apt to develop a cardiometabolic disease. Blood samples were collected from 42 subjects in Mala (30 m - Lima) and from 65 people native to Carhuamayo (Junin 4100 m). Weight, height and blood pressure were measured. Hemoglobin (Hb) was determined in whole blood; glucose, total cholesterol, high density lipoproteins, triglycerides and MPO were determined in serum. The results show that with the exception of weight, height and Hb, no significant gender differences between the averages of other variables in both groups were observed. When comparing both populations, highly significant differences in weight (< 0,001), BMI (< 0,001), Hb (< 0,001), glucose (< 0,001) and MPO (< 0,01) were found. Hb levels were higher in the population of Carhuamayo, while the weight, BMI, glucose and MPO were significantly lower than the sea level means. Positive significant correlation between MPO and weight, waist, BMI and glucose was observed. It was concluded that the myeloperoxidase (MPO) would not be a risk factor for cardiometabolic disease in Andean populations.